Propuesta del Proceso de Implementación de una Ventanilla Única de Servicios en Línea para el Departamento de Recaudación en la Gestión de Trámites Públicos del Gobierno Autónomo Descentralizado del Cantón Gonzanamá, año 2022 - Granda Figueroa, Alisson Fabian (2023)
The project was focused on proposing a process for the implementation of a single window for online services for the collection department of the Decentralized Autonomous Government of the Gonzanamá Canton. For this purpose, the processes of entry, exit, situational diagnosis, as well as the limitations inherent to the entity were taken into account: scarce technological infrastructure and the lack of standardization of the process in question. Thus, in order to prepare the process manual and the ICT implementation proposal, it was necessary to be based on results-based management and quality management, in order to structure a transformation and institutional modernization strategy. The methodology used was a mixed approach and descriptive in scope, through which various instruments for collecting information, surveys, interviews and direct observation were applied, which allowed determining the situational diagnosis of the collection department. The analytical-synthetic method was also used to identify the activities and procedures that served as the basis for developing the ICT manual and proposal. Finally, the most relevant aspects in the formulation of results, conclusions and recommendations were synthesized.